The assessment of the complexity of rural poverty : the case of the Mtumbane Community - Zipete, D. Z.(Devillier Zithandele) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.P.A.) -- University of Stellenbosch, 1998.